2014
DOI: 10.1371/journal.pone.0105582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caste on the Expression of Genes Associated with Septic Injury and Xenobiotic Exposure in the Formosan Subterranean Termite

Abstract: As social insects, termites live in densely populated colonies with specialized castes under conditions conducive to microbial growth and transmission. Furthermore, termites are exposed to xenobiotics in soil and their lignocellulose diet. Therefore, termites are valuable models for studying gene expression involved in response to septic injury, immunity and detoxification in relation to caste membership. In this study, workers and soldiers of the Formosan subterranean termite, Coptotermes formosanus, were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 92 publications
(127 reference statements)
1
12
0
Order By: Relevance
“…The social insect colony is a highly organization society with specialized castes. Previous studies in termites have revealed caste specific expression patterns that reflect the specialized functions of castes within colony (Husseneder and Simms, 2014;Jones et al, 2017;Mitaka et al, 2017;Mitaka et al, 2016;Scharf et al, 2003). In this study, we show that constitutive immune gene expression is strongly caste specific in N. castaneus, reflecting a division of social roles and indicating a significant degree of caste-specific immune defense.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The social insect colony is a highly organization society with specialized castes. Previous studies in termites have revealed caste specific expression patterns that reflect the specialized functions of castes within colony (Husseneder and Simms, 2014;Jones et al, 2017;Mitaka et al, 2017;Mitaka et al, 2016;Scharf et al, 2003). In this study, we show that constitutive immune gene expression is strongly caste specific in N. castaneus, reflecting a division of social roles and indicating a significant degree of caste-specific immune defense.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses a sterile soldier caste, a reproductive caste and so-called false workers, which carry out shared tasks such as proctodeal trophallaxis and allogrooming (Davis et al, 2018;De Bie et al, 2006), while retaining the physiological capacity to develop into reproductive individuals under the right colony conditions (Korb and Hartfelder, 2008) . The subsocial wood feeding, C. meridianus, which represents the key lineage of Cryptocercus that is important in any comparative analysis of termite evolution because of important transitional traits such as subsociality, a wood diet with associated protist gut symbionts, and developmental similarities with termites (Inward et al, 2007a;Lo and Eggleton, 2010;Nalepa, 2015 For sequencing, equal amounts of total RNA from 8 and 4 injected individuals were pooled for termites and cockroaches for each treatment for library preparation, respectively. Each caste, species and treatment were represented by 2 libraries (N= 12, 4 and 4 total libraries for N. castaneus, C. meridianus and B. orientalis, respectively).…”
Section: Individual Immune Challenge Experimentsmentioning
confidence: 99%
See 3 more Smart Citations